Mystery of neck lump: an uncommon presentation of urachal cancer. Issue 8 (26th August 2019) - Sahu, Kamal Kant; Pandey, Deepali; Mishra, Ajay Kumar; O'Shea, James; Chen, Yayan; McGregor, Bradley
Abstract : We present the case of a 55-year-old male patient who presented with palpable cervical lymphadenopathy. Excisional biopsy showed metastatic adenocarcinoma of unknown origin. Imaging showed a bladder mass following which he underwent transurethral resection of bladder tumour. Histopathological evaluation of mass confirmed a poorly differentiated adenocarcinoma with signet-ring cell features. Immunohistochemistry was suggestive of metastatic urachal cancer. He agreed for enrollment in a clinical trial, however soon after 1st cycle, he developed immune pneumonitis requiring high dose steroids. On follow-up, MRI brain was done for evaluation of headache which showed metastatic intracranial disease. He completed radiotherapy following which he was started on FOLFOX chemo regimen (folinic acid, 5-fluorouracil and oxaliplatin).